1989
DOI: 10.1002/1097-0142(19890701)64:1<116::aid-cncr2820640121>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two methods of parenteral nutrition support in improving muscle mass of children with neuroblastoma or Wilms' Tumor. A randomized study

Abstract: The short-term and long-term effectiveness of central parenteral nutrition (CPN) versus peripheral parenteral nutrition (PPN) in improving muscle mass (arm muscle area [AMA]) was evaluated for 24 malnourished children with newly diagnosed Stage IV neuroblastoma (n = 14) or Stages II-V Wilms' tumor (n = 10). Patients were randomized to either CPN or PPN plus enteral nutrition (EN: intense nutrition counseling, oral foods, and supplements) for 4 weeks followed by EN until week 10. Oncologic treatment was similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It has been described in resource rich settings that nutritional support either with parenteral nutrition or via a gastric tube can improve nutritional status of patients with Wilms tumour during therapy 25, 26. Different protocols and guidelines exist as to when to start this type of nutritional support 27.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described in resource rich settings that nutritional support either with parenteral nutrition or via a gastric tube can improve nutritional status of patients with Wilms tumour during therapy 25, 26. Different protocols and guidelines exist as to when to start this type of nutritional support 27.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers claim that children with cancer have a high incidence of wasting and stunting (Rickard et al, 1983a,b;Kibirige et al, 1988;Rickard et al 1989a;(Berry et al, 1983), even at the time of diagnosis, compared to a healthy population. Others do not support the above ®nding (Donaldson et al, 1981;Carter et al, 1983b;Besscho 1986;Tamminga et al, 1990).…”
Section: Indications For Bone Marrow Transplantation As Determinants mentioning
confidence: 99%
“…6 Similar observations were found in other studies 19,[21][22][23] We studied the impact of nutritional status on the disease pattern i.e., incidence of relapse, treatment 6 Various other studies have also found similar results of malnourished child by WFH. [24][25][26][27] Roy et al found that under nutrition adversely affect the final outcome, treatment tolerance and treatment complications in children with ALL. 14 Zalina et al did not find significant differences in the nutritional status among a sample of children with leukemia at different stages of treatment.…”
Section: Discussionmentioning
confidence: 99%